PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN DI SEKOLAH DASAR - Panji Maulana; Aulia Akbar (Universitas Syiah Kuala, 2017)
This research is motivated that reading skills of elementary school students in Indonesia is still low, h al is evidenced by the results of test data from PIRLS (Progress in International Reading Literacy Study) which is an international study in the field of reading in children worldwide are sponsored by The International Association for the Evaluation Achievement (IAEA), produce that Indonesia is fourth from the bottom, followed by 45 countries in 2006 (IEA, 1992; Asia's Weeks, 1997 in Iskandarwassid and Dadang Sunendar: 2008: 245-245). Therefore, researchers will conduct research in the fifth grade of primary school as its object by using STAD type of cooperative learning. The purpose of this study is to improve reading comprehension and motivation of the students' reading, describe the steps and process / implementation of learning in reading comprehension by implementing cooperative learning STAD (Student Teams Achievement D iv ision), and m e ndeskripsikan whether there is an increase in reading comprehension by implementing cooperative learning STAD (Student Teams Achievement Division) in class V SDN Santaka districts Cimanggung. The method used is the PTK (Classroom Action Research) with d esign of the research refers to a model developed by Kemmis and Taggart, the spiral model starts with: 1) planning (pla n ning); 2) the action / action (acting); 3) observation (observing); and 4) reflection (reflecting). The subjects were students of class V SDN Santaka totaling 30 people. This study was conducted for 3 cycles. The research data was collected through observation to observe students directly at the time of the learning process, interviews were conducted to determine the students 'attitudes toward the use of the cooperative model STAD in teaching reading comprehension, and t es outcomes study was conducted to determine the increase in the ability of students' reading comprehension and t ice is given in the form of a description.